TIMBULAN SAMPAH PADA TEMPAT PENAMPUNGAN SAMPAH SEMENTARA (TPS) YANG AKAN MENERAPKAN REDUCE,REUSE, RECYCLE (TPS 3R) KELURAHAN WONOREJO KOTA SURABAYA - Euis Nurul Hidayah; Emeraldi Firdaus (EnviroUS, 2022)
The amount of waste generated by the people of Surabaya in 2020 reached 2,913.18 tons per day. With an increasing population growth rate as happened in Wonorejo Village, Surabaya City, which has a high population growth rate. This study aims to determine the amount of waste generated at the TPS. The method used for sampling and measurement is SNI 19-3964-1994. Based on the results of sampling, the amount of waste generated in Wonorejo Village is 2.94 m3/person/day. Then the average composition of organic waste is easy to decompose, organic waste is difficult to decompose, and inorganic waste is 44.3%, 1.3%, and 54.5%, respectively.